FISH studies in a patient with sporadic aniridia and t(7;11) (q31.2;p13). Issue 1 (January 1996) - Crolla, J A; Cross, I; Atkey, N; Wright, M; Oley, C A
Abstract : A 2 year old female presenting with bilateral sporadic aniridia was found to have an apparently balanced reciprocal translocation with a chromosome 11 breakpoint within band p13. Fluorescence in situ hybridisation (FISH) studies with distal 11p13 specific cosmids showed that the chromosome 11 breakpoint lay between the aniridia (PAX6) locus and a region approximately 100 kb distal to PAX6 defined by the cosmid FO2121. Although this patient did not have a detectable deletion within PAX6, her aniridia may have resulted from a disruption of the distal chromatin domain containing either enhancers or regulators for PAX6. This case may therefore be another example of aniridia caused by a position effect as recently described in two familial aniridia patients in which the phenotype cosegregated with chromosome abnormalities with 11p13 breakpoints.